PENGEMBANGAN MEDIA GAME ULAR TANGGA BERBASIS KERAGAMAN BUDAYA UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS - Widiyastuti; Yetty Trisnayanti; Cahyo Dwi Andita (Linggau Journal Science Education (LJSE), 2026)
This study aimed to develop a Culture Diversity-Based Snakes and Ladders Game Media in IPAS learning that is valid, practical, and effective in improving elementary school students’ learning outcomes. The type of research used was Research and Development (R&D) with the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were fourth grade 23 students of SD Negeri 43 Lubuklinggau. Data collection techniques were carried out through questionnaires, tests, and documentation. Based on the results of the validation recapitulation conducted by language experts, material experts, and media experts, an average percentage of 92% was obtained with a very valid category, so the media was declared feasible for use in learning. The practicality test results obtained through teacher trials, one-to-one trials, and small group trials showed an average percentage of 93% with a very practical category, which means the media is easy to use in the learning process. Furthermore, the effectiveness test results through the calculation of N-Gain from pretest and posttest scores showed a score of 0.83 with a high classification. The average pretest score of students was 38 and increased to 90 in the posttest score, indicating that the use of Culture Diversity-Based Snakes and Ladders Game Media was effective in improving student learning outcomes in IPAS learning for fourth grade students at SD Negeri 43 Lubuklinggau. Based on these results, it can be concluded that the developed Culture Diversity-Based Snakes and Ladders Game Media is proven to be very valid, very practical, and effective for use in the IPAS learning process in elementary schools.